SELEKSI JENIS TUMBUHAN PAKAN DAN KANDUNGAN NUTRIEN JENIS TUMBUHAN YANG DIMAKAN SAPI BALI (Bos sondaicus) LEPAS SAPIH DI DAERAH BUKIT BADUNG SELATAN, KABUPATEN BADUNG, BALI - Heri Dismawan, I Wayan; Ginantra, I Ketut; Ni Luh Suriani, Ni Luh (SIMBIOSIS, 2014)
This study was conducted to determine the plants species and nutrient content of plant species selected by weaning of bali cattle in South Badung Hill, Badung regency, Bali. Study was conducted in three Grazing unit Bali cattle are Sawangan, Kutuh and Pecatu. In December 2013 to February 2014. Determination of the composition of plant species in the habitat (n?) is determined by the square method. Determination of plants composition in diet (r?) determined by utilization methods. This method is based on the percentage bite mark of plants species in plot sampling. Nutrient content was analyzed crude protein, energy, calcium and phosphorus. Crude protein determination with a Semi-micro Kjeldahl technique and energy content by Bomb Calorimeter. Determination of mineral content of calcium (Ca) and Phosphorus (P) by using Atomic Absorption Spectrophotometer (ASS). Tests carried out in the Laboratory of Nutrition and Forage Analytical Chemistry, University of Udayana. The JURNAL SIMBIOSIS II (2): 192- 202 ISSN: 2337-7224 Jurusan Biologi FMIPA Universitas Udayana September 2014 results study showed 32 species of plants available in the habitat, there are nine species of plants that are selected by weaning bali cattle, that are Desmodium heterofilum, Pleura interupta, Polygala glomerata, Cyperus rotundus, Desmodium triflorum, Dactyloctenium aegyptium, Portulaca sp. Polygala chinensis, and Panicum eruciforme. Nutrient content of plant species eaten a protein ranged from 11.25% - 17.14%, GE 3.10 kcal / g - 4.11 kcal / g, Ca 0.33% - 1.86%, and 0.026% P - 0.24%. Keywords: Weaning bali cattle, plants selected species, nutrient content